2013
DOI: 10.1038/bjc.2013.475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prognostic factors in liver-limited metastatic colorectal cancer: a preplanned analysis of the FIRE-1 trial

Abstract: Background:Liver-limited disease (LLD) denotes a specific subgroup of metastatic colorectal cancer (mCRC) patients.Patients and Methods:A total of 479 patients with unresectable mCRC from an irinotecan-based randomised phase III trial were evaluated. Patients with LLD and non-LLD and hepatic resection were differentiated. Based on baseline patient characteristic, prognostic factors for hepatic resection were evaluated. Furthermore, prognostic factors for median overall survival (OS) were estimated via Cox regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
5
22
0
3
Order By: Relevance
“…Other investigators have also shown LDH is a strong factor [11]. While serum CEA is the most commonly performed serum tumor marker in this patient population, our study validates the additional importance of serum LDH.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other investigators have also shown LDH is a strong factor [11]. While serum CEA is the most commonly performed serum tumor marker in this patient population, our study validates the additional importance of serum LDH.…”
Section: Discussionsupporting
confidence: 87%
“…LDH is a metabolic enzyme that catalyzes the conversion of pyruvate to lactate under anaerobic conditions and is overproduced in cancer cells [8]. Several studies have demonstrated a negative association between elevated LDH and OS [9][10][11]. CEA is a glycoprotein involved in cell adhesion, immunity and apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…In clear contrast, LLD status was associated with secondary hepatic resection leading to an excellent median OS of 56.2 months. This compares well to previous findings from unselected patients who had been treated with chemotherapy only . In the FIRE‐1 trial comparing FUFIRI to mIROX, median OS was 48 months in LLD patients who became resectable during treatment.…”
Section: Discussionsupporting
confidence: 85%
“…LDH is a metabolic enzyme that catalyzes the conversion of pyruvate to lactate under anaerobic conditions and is over‐produced in cancer cells . Several studies have demonstrated a negative association between elevated LDH and OS . CEA is a glycoprotein involved in cell adhesion, immunity, and apoptosis .…”
Section: Introductionmentioning
confidence: 99%